Whatsapp Reminder Care: As An Effort to Strengthen The Birth Preparedness And Complication Readiness (BPCR) And Preparedness of Pregnant Women in The Flood-Prone Area Pantai Cermin Community Health Center Tanjung Pura - Ziadatun Amini Harahap; Eliza Bestari Sinaga; Meni Fuzi Astuti Tanjung; Dwi Cahaya Pranesti (Jurnal Ners, 2026)
The Pantai Cermin Tanjung Pura Health Center area is highly vulnerable to seasonal flooding, which disrupts pregnant women’s access to health services. The low coverage of antenatal care (ANC) and Birth Preparedness and Complication Readiness (BPCR) in Indonesia increases the risk of delayed treatment and pregnancy complications among pregnant women in flood-prone areas. This study aimed to analyze BPCR levels before and after the WhatsApp Reminder intervention, examine its effectiveness in improving childbirth preparedness, and develop an applicable and replicable implementation model. This study used a quasi-experimental pre–post test with control group design. The study population consisted of pregnant women registered in the maternal and child health register at Pantai Cermin Health Center, with a total sample of 100 respondents divided into 50 intervention groups and 50 control groups using purposive sampling techniques. The intervention was conducted through educational WhatsApp reminder messages for 12 weeks. Data were analyzed using comparative tests and ANCOVA to control confounding variables. The results showed that WhatsApp Reminder Care was effective in improving BPCR among pregnant women in flood-prone areas, indicated by an increase in the average BPCR score in the intervention group compared to the control group. In addition, this study produced a digital intervention model based on WhatsApp broadcast that is applicable, standarized, and easy to replicate in maternal health services in disaster-prone areas. Therefore, it is recommended that healthcare workers, especially midwives at community health centers, continue to develop this intervention as a digital technology-based health promotion medium for pregnant women.